An intelligent approach for qualified voting in P2P mobile collaborative team: a comparison study for two fuzzy-based systems. (2017) - Liu, Yi; Ozera, Kosuke; Matsuo, Keita; Barolli, Leonard
Mobile computing has many application domains. One important domain is that of mobile applications supporting collaborative work. In a collaborative work, the members of the team have to take decision or solve conflicts in project development and therefore members have to vote. In this work, we present a voting model, that we call qualified voting, in which every member has a voting score according to four parameters: number of activities that member participates (NAMP), number of activities that member successfully finished (NAMSF), number of online discussions that member participated (NODMP), number of activities the member fails (NAMF). Then, we use fuzzy approach to compute a voting score for the member. We present two fuzzy based voting systems (called FPVS1 and FPVS2). The simulation results show that when NAMP, NAMSF and NODMP are high, the voting score is high, but with increasing of the NAMF, the VS is decreased. Comparing the complexity of FPVS1 and FPVS2, the FPVS2 is more complex than FPVS1, but FPVS2 can select better peers for the collaborative work.